2007
DOI: 10.1073/pnas.0705873104
|View full text |Cite
|
Sign up to set email alerts
|

Mg 2+ mediates interaction between the voltage sensor and cytosolic domain to activate BK channels

Abstract: The voltage-sensor domain (VSD) of voltage-dependent ion channels and enzymes is critical for cellular responses to membrane potential. The VSD can also be regulated by interaction with intracellular proteins and ligands, but how this occurs is poorly understood. Here, we show that the VSD of the BK-type K ؉ channel is regulated by a state-dependent interaction with its own tethered cytosolic domain that depends on both intracellular Mg 2؉ and the open state of the channel pore. Mg 2؉ bound to the cytosolic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(154 citation statements)
references
References 44 publications
7
145
1
Order By: Relevance
“…This result is consistent with the location of D367 that is close to the VSD of the channel in the membrane (9,10). Previous results have demonstrated that the cytosolic domain interacts with the VSD during BK channel activation (28,29), and such interactions may result in a weak voltage dependence of Ca 2+ sensitivity derived from the RCK1 site (17). Thus, it is possible that the mutation D367A also alters function of the VSD, resulting in changes of voltage-dependent activation.…”
Section: +supporting
confidence: 78%
See 1 more Smart Citation
“…This result is consistent with the location of D367 that is close to the VSD of the channel in the membrane (9,10). Previous results have demonstrated that the cytosolic domain interacts with the VSD during BK channel activation (28,29), and such interactions may result in a weak voltage dependence of Ca 2+ sensitivity derived from the RCK1 site (17). Thus, it is possible that the mutation D367A also alters function of the VSD, resulting in changes of voltage-dependent activation.…”
Section: +supporting
confidence: 78%
“…The Mg 2+ ion bound to the interface between the VSD and RCK1 activates the BK channel by an electrostatic repulsion to the S4 segment (28). These results suggest that RCK1 is located close to the VSD and the two domains interact intimately, which is corroborated by an electron cryomicroscopy (cryo-EM) structure of BK channels (33).…”
Section: +supporting
confidence: 64%
“…Previous studies showed that Mg 2ϩ binds at VSD-CTD interface of Slo1 channels with two coordinate residues (D99 and N172) from VSD and another two (E374 and E399) from CTD ( Fig. 1; Shi et al, 2002;Xia et al, 2002;Yang et al, 2008a). The bound Mg 2ϩ interacts with gating charge R213 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that Mg 2ϩ binds in between the VSD and CTD interface of Slo1 and interacts with gating charge R213 in S4 to activate the channel (Yang et al, 2007(Yang et al, , 2008aFig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism seems to be another: bound Mg 2+ is suggested to electrostatically repel one of the positively charged arginines in the C-terminal part of S4 [219,220]. This shows that cytosolic domains can be close enough to the VSD to have an electrostatic impact.…”
Section: Binding Of Cyclic Nucleotides and Ca 2+ To Specific Domainsmentioning
confidence: 99%